2005
DOI: 10.1074/jbc.m501564200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus DNA-negative Dane Particles Lack Core Protein but Contain a 22-kDa Precore Protein without C-terminal Arginine-rich Domain

Abstract: DNA-negative Dane particles have been observed in hepatitis B virus (HBV)-infected sera.The capsids of the empty particles are thought to be composed of core protein but have not been studied in detail. In the present study, the protein composition of the particles was examined using new enzyme immunoassays for the HBV core antigen (HBcAg) and for the HBV precore/core proteins (core-related antigens, HBcrAg). HBcrAg were abundant in fractions slightly less dense than HBcAg and HBV DNA. Three times more Dane-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
130
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 40 publications
5
130
1
Order By: Relevance
“…Therefore, the measurement of intrahepatic HBV DNA and/or HBV cccDNA is important for monitoring the viral status of hepatitis patients [Sung et al, 2005], although these assays involve the physical stress of needle biopsy. Several reports indicate that the level of HBcrAg, which is a complex of HBeAg, HBcAg, and p22cr coding precore/core gene [Kimura et al, 2002[Kimura et al, , 2005, reflects the natural course of viral loads in patients under treatment with nucleos(t)ide analogues, and that the reduction rate of HBcrAg is slower than that of serum J. Med. Virol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the measurement of intrahepatic HBV DNA and/or HBV cccDNA is important for monitoring the viral status of hepatitis patients [Sung et al, 2005], although these assays involve the physical stress of needle biopsy. Several reports indicate that the level of HBcrAg, which is a complex of HBeAg, HBcAg, and p22cr coding precore/core gene [Kimura et al, 2002[Kimura et al, , 2005, reflects the natural course of viral loads in patients under treatment with nucleos(t)ide analogues, and that the reduction rate of HBcrAg is slower than that of serum J. Med. Virol.…”
Section: Discussionmentioning
confidence: 99%
“…p22cr is a precore protein from amino acid À28 to at least amino acid 150, containing an uncleaved signal sequence and lacking the C-terminal arginine-rich domain. p22cr is found in empty and HBV DNA negative virus particles; the production of empty particles is not dependent on the formation of HBV DNA [Kimura et al, 2005]. Several reports indicate that the concentration of serum HBcrAg is closely correlated with peripheral HBV DNA in untreated patients [Rokuhara et al, 2003;Tanaka et al, 2006].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, HBcAg, the major protein of the HBV capsid, is translated from HBV pregenomic mRNA 21 . Since HBeAg and HBcAg share a sequence consisting of 149 amino acids, they are collectively called Hepatitis B core-related antigens.…”
Section: Discussionmentioning
confidence: 99%
“…It would also allow for a comparison of the efficacies of potent antiviral drugs when a large proportion of patients have HBV DNA below the detection threshold 21 . ROKUHARA et al 29 reported that five out of six patients treated with LAM for six to eight months still had detectable levels of core-related antigen.…”
mentioning
confidence: 99%